Religious behavior among university students (Journal of the College of Basic Education, 2023)
The idea of religion is an idea as old as man himself, and this is indicated by many studies.anthropology as well as the evidence reported by paleontologists and archaeologists. Religion is a necessityIt is indispensable to man in his life, as all religions, despite their different foundations,and beliefs, but they share one goal, which is to provide security and reassurance to man and help himto organize his social life, because it contains systems and methods that organize the lives of individualsgroups, whether in terms of their personal, economic or social